Avaliação da distribuição de tensões nas facetas estéticas de porcelana pelo método de elementos finitos - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2005)
The present work had the objective to evaluate the distribution of tensions in teeth restored with aesthetic porcelain laminates by the finites elements method, in representative models of upper incisors central, where three types of simulation had been used: teeth that did not present dental preparations with and without covering of the incisal edge, and teeth that had preparation in shoulder form and layering of the incisal edge. These models had been submitted to the loads of 100N and 350 N in the incisal edge, under angles of 450 and 900, simulating clinical conditions of carrying patients of class I of the Angle and patients with direct bite of the incisors and/or bruxomanos. We observed that the increase of the load, as well as the reduction of the angulations, had promoted an increase to the tensions in the representative models of porcelain laminate, and that the models represented by the lithium dissilicato porcelain, presented a better behavior in relation to the distribution of the tensions on teeth restored with feldspática porcelain laminate.
Keywords: elemento finito; facetas laminadas de porcelana; crâmicas; finite element; laminate veneers porcelain; ceramics; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA